Application of Thyroid Imaging Reporting and Data System in the Ultrasound Assessment of Thyroid Nodules According to Physician Experience. Issue 2 (June 2016) - Ko, Su Yeon; Kim, Eun-Kyung; Moon, Hee Jung; Yoon, Jung Hyun; Kim, Ha Yan; Kwak, Jin Young
Abstract : Objective: The aim of this study was to investigate and compare the diagnostic performances of the Thyroid Imaging Reporting and Data System (TIRADS) in differentiating benign and malignant thyroid nodules according to the level of physician experience. Materials and Methods: From March to October 2013, 1102 patients with 1128 thyroid nodules who underwent initial ultrasound-guided fine needle aspiration were included in this study. Thyroid nodules were categorized according to TIRADS. Diagnostic performances of ultrasound were compared according to performer experience using the χ 2 test or Fisher exact test. Results: Of 1128 thyroid nodules, 281 were malignant, and 847 were benign. The risk of malignancy of each TIRADS category by the experienced and less experienced physicians were as follows: category 3 (0.9% vs 0%), category 4a (3.5% vs 1.3%), category 4b (7.3% vs 12.1%), category 4c (67.5% vs 44.9%), and category 5 (97.7% vs 76.5%). Sensitivity, specificity, accuracy, positive predictive value, and negative predictive value were 99.1%, 35.9%, 52.5%, 35.5%, and 99.1%, respectively, for experienced physicians and 100%, 20.9%, 37.6%, 35.2%, and 100%, respectively, for less experienced physicians. Specificity, accuracy, and positive predictive value were statistically higher for experienced physicians than those for less experienced physicians ( P < 0.001, 0.001, and 0.004). There was a significant difference in areas under the curve between the 2 groups ( P < 0.001). Conclusions: In conclusion, the diagnostic performance of the stratification of malignancy risk according to TIRADS categories was comparable between the experienced and less experienced physician groups. The application of TIRADS is reproducible, and it was easy to predict the probability of thyroid malignancy in both the experienced and less experienced physician groups.